ANALISIS PENGUASAAN KALIMAT “OBJEK GANDA” PADA MAHASISWA ANGKATAN 2017 UNIVERSITAS TANJUNGPURA - Desi Oktarianti; Ina Ina; Bun Yan Khiong (Universitas Tanjungpura, 2019)
AbstractIn the process of learning Mandarin language, the student would learned grammar.